Oral Intragastric DMBA Administration Induces Acute Lymphocytic Leukemia and Other Tumors in Male Wistar Rats - El-Masry OS; Alhawaj HA; Fagere MO; Owaidah AY; Alamri A; Alsamman K (Dove Medical Press, 2022)
Omar S El-Masry,1 Hussain Abdullah Alhawaj,2 Muaz O Fagere,1 Amani Y Owaidah,1 Aisha Alamri,1 Khaldoon Alsamman1 1Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, Imam Abdulrahman Bin Faisal University, Dammam, 31441, Saudi Arabia; 2Animal House Facility, Institute for Research and Medical Consultations, Imam Abdulrahman Bin Faisal University, Dammam, 31441, Saudi ArabiaCorrespondence: Khaldoon Alsamman, Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, Imam Abdulrahman Bin Faisal University, Dammam, 31441, Saudi Arabia, Email kmalsamman@iau.edu.saBackground: Animal models of blood cancer are important tools to study these malignancies and also screen for novel therapeutic agents. Evidence from past research on the carcinogenic properties of 7,12-dimethylbenz[a]-anthracene (DMBA) was provided by a handful of studies. However, recent literature on DMBA carcinogenic activity and the underlying mechanisms is scarce.Objective: The aim of this study was to develop a chemical model of leukemia using DMBA. Male Wistar rats (6 weeks old) were administered 1.5 mg of DMBA dissolved in sesame oil in biweekly doses using oral intragastric intubation.Materials and Methods: Frequent complete blood counts and blood smear morphology assessment were used to assess the development of leukemia, while gross pathology and histopathology staining were used to evaluate malignancy development.Results: The results showed that only 4% of rats developed acute lymphocytic leukemia. Interestingly, 36% of the rats developed tumors (parotid tumors [24%] and fibrosarcomas [12%]).Conclusion: These results suggest the pleiotropic potential of DMBA in the induction of multiple types of malignancies, including leukemia. This could be used as a model to validate therapeutic targets for leukemia and other induced malignancies.Keywords: 7, 12-dimethylbenz[a]-anthracene, DMBA, leukemia, parotid gland, fibrosarcoma